Expanding the canvas of PRKN mutations in familial and early-onset Parkinson disease. (September 2019) - Pandey, Sanjay; Tomar, Laxmikant Ramkumarsingh; Kumar, Sumeet; Dinesh, Shreya; Thelma, B.K.
Abstract: Background: Mutations in PRKN (PARK2) are commonly encountered in early-onset Parkinson disease (PD). Objectives: To screen for PRKN mutations in a clinically well-characterized cohort of early-onset PD patients with a family history (FEOPD; ≤50 years at onset) or sporadic (SEOPD; ≤50 years at onset) and late-onset familial patients (FLOPD; >50 years at onset). Methods: A total of 97 patients including 52 SEOPD and 45 familial PD (FEOPD: 23; FLOPD: 22) were screened for variants in PRKN by PCR- Sanger sequencing. PRKN dosage and variants in known PD genes were screened by qPCR and whole-exome sequencing in a subset of samples. Results: A total of 25 (25.77%) patients (SEOPD: 12, FEOPD: 6, and FLOPD: 7) were positive for PRKN variants. Of these, two patients manifested homozygous variants; while one patient was carrying three PRKN variants and two patients were carrying two PRKN variants. But, we could not examine their parents or relatives and their genotypes remain unknown. The remaining 20 (80%) patients were carrying heterozygous variants only. 32% of these variants were in exon 2, including a novel truncating homozygous variant( c.97C > T:p.Arg33Ter) in a SEOPD patient. Conclusion: In our cohort, a novel homozygous variant( c.97C > T:p.Arg33Ter) in a patient with hyperhidrosis expands the spectrum of PRKN associated mutations. Furthermore, ~80% of the PRKN variants being heterozygous in this study cohort, implies the utility of the cohort for identification of additional novel/known causative PD gene(s). Highlights: Early-onset and familial Parkinson disease patients were screened for PRKN mutation. A total of 25.77% (25/97) patients were positive for PRKN mutations. The majority (20; 80%) were carrying heterozygous variants only. A novel homozygous variant (c.97C > T:p.Arg33Ter) was reported in one patient.